The Asian American movement - Wei, William, 1948- (Asian American history and culture., 1993)
Largely unexamined until recently, the Asian American Movement has been active for more than two decades. William Wei traces to the late 1960s the initial genesis of an Asian American identity, culture, and activism through which members of this pan-Asian group could assert their right to belong to and be respected as responsible members of this society. Although its antecedents were the civil rights and Black Power movements, the Asian American Movement actually resulted from the protests against the Vietnam War and the emergence of a generation of college-aged Chinese and Japanese Americans. In this definitive study of the Asian American Movement, Wei fills an important gap in our knowledge of ethnic social movements and the struggle to achieve American cultural democracy. Lacking a nationally known leader but confronted by many shared issues and concerns, the Asian American Movement was essentially a middle-class reform effort to achieve racial equality, social justice, and political empowerment. It focused on ethnic solidarity and self-empowerment through political activism, educational and community development, and cultural expressions. While the Movement was most visible on the West Coast, notably at the Third World Strike at San Francisco State College in 1968, it became a vital force simultaneously on campuses and in Asian American communities throughout the country. Wei evaluates the Movement's effort to develop a unique but cohesive ethnic identity and the internal struggles between reformist and revolutionary approaches to social change. He analyzes the Asian American women's movement, the alternative press, Asian American studies programs, community-based organizations, and Maoist sects. His study concludes with an examination of Asian American involvement in electoral politics and the quest for political empowerment. Interviews with many of the key participants in the Movement and photographs of Asian American demonstrations and events enhance Wei's portrayal of the development and breadth of the Movement and the conflicts within it. Exploring regional differences; issues of ethnicity, class, and gender; and the transition from radical to electoral politics, Wei's comprehensive study is the first book to examine systematically the coming-to-consciousness and mobilization of Asian Americans.